Human emotional response to steering wheel vibration in automobiles. (1st January 2013) - Ajovalasit, Marco; Tajadura-Jiménez, Ana; Shabani, Arber; Giacomin, Joseph
This study investigates what form of correlation may exist between measures of the valence and the arousal dimensions of the human emotional response to steering wheel vibration and the vibration intensity metrics obtained by means of the unweighted and the frequency weighted root mean square (rms). A laboratory experiment was performed with 30 participants who were presented 17 acceleration time histories in random order and asked to rate their emotional feelings of valence and arousal using a self-assessment manikin (SAM) scale. The results suggest a highly linear correlation between the unweighted, Wh weighted and Ws weighted vibration intensity metrics and the arousal measures of the human emotional response. The results also suggest that while vibration intensity plays a significant role in eliciting emotional feelings, there are other factors which influence the human emotional response to steering wheel vibration such as the presence of high peaks or high frequency band amplitudes.